Breathable functional aerogel dressings facilitate the healing of diabetic wounds - Mingyue Liu; Yu Chen; Yu Zhang; Pengzhen Zhuang; Juan Wang (Biomedical Technology, 2025)
Due to the complexity of the microenvironment and healing process of diabetic wounds, developing wound dressings that offer good biocompatibility, breathability, and promote vascular regeneration is essential but remains a significant challenge. In this study, we prepared loose and porous aerogel wound dressings using electrospinning and freeze-drying methods with natural polymer compounds: gelatin, polylactic acid, and magnesium oxide nanoparticles (MgO) as raw materials. MgO serves as a functional modification component that regulates the wound microenvironment and promotes vascular regeneration by releasing bioactive ions, thereby facilitating wound healing. Additionally, this scaffold provides excellent breathability and exudate management due to its loose porous structure. These advantages enable the aerogel scaffold to effectively promote collagen deposition and neovascularization, accelerating the healing of diabetic infected wounds.